South Africa ID Case Study - World Bank Group (World Bank, Washington, DC, 2019)
South Africa’s approach to identification offers valuable lessons for countries looking to increase the coverage, robustness, and use of their ID systems. Since the end of apartheid, South Africa’s national identification system has been transformed from a tool of oppression to one for inclusion and the delivery of social services. The ID system is now closely integrated with civil registration, boasts high coverage among all segments of the population, and has been instrumental for effective service delivery and a cost effective electoral process.